2013
DOI: 10.1164/rccm.201209-1749oc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Complex–expanded Natural Killer Cells Improve Allogeneic Lung Transplant Function via Depletion of Donor Dendritic Cells

Abstract: These results suggest that NK cells favor allograft acceptance by depleting donor-derived DCs, which otherwise would prime alloreactive T-cell responses. Thus, conditioning regimens that augment NK-cell reactivity should be clinically explored to prepare lung allograft recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
3
34
1
Order By: Relevance
“…In this study, the mouse NKG2D ligand Rae-1 had increased expression in allografts, overexpression of Rae-1 resulted in severe luminal fibrosis even in the absence of T or B cells and an antibody blocking NKG2D prevented this luminal fibrosis 51. Notably, these findings contrast with the study by Jungraithmayr et al ,26 where augmentation of NK cells by IL-15/IL-15Rα complex therapy before transplant resulted in depletion of APCs and protection from rejection pathology. Together these two studies suggest that magnitude, timing and context of NK cell responses may differentiate between protective versus destructive graft responses.…”
Section: Introductioncontrasting
confidence: 89%
“…In this study, the mouse NKG2D ligand Rae-1 had increased expression in allografts, overexpression of Rae-1 resulted in severe luminal fibrosis even in the absence of T or B cells and an antibody blocking NKG2D prevented this luminal fibrosis 51. Notably, these findings contrast with the study by Jungraithmayr et al ,26 where augmentation of NK cells by IL-15/IL-15Rα complex therapy before transplant resulted in depletion of APCs and protection from rejection pathology. Together these two studies suggest that magnitude, timing and context of NK cell responses may differentiate between protective versus destructive graft responses.…”
Section: Introductioncontrasting
confidence: 89%
“…Direct allorecognition alone can result in acute rejection (AR), even without indirect mechanisms (2). Furthermore, depletion of donor immune cells from an organ prior to transplantation prevents rejection (3), and restoration re-establishes the alloresponse (4). It therefore appears that clinical outcome following transplantation is dependent on the early processes of recipient allorecognition of donor antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments indicated that the mechanism by which NK cells confer protection may be through removal of donor-derived dendritic cells from the allograft. These results provide an opportunity to consider whether preconditioning of lung recipients with regimens that augment NK cell reactivity may be beneficial for transplant outcomes (33).…”
Section: Mechanisms and Predictors Of Rejectionmentioning
confidence: 95%